POLIMORFISME GENA RESEPTOR MCP-1 (CCR2) SEBAGAI FAKTOR RISIKO NEFROPATI DIABETIKA PADA PENDERITA DIABETES MELLITUS TIPE 2 DI RSUD PROF DR MARGONO SOEKARJO DAN RSUP SARDJITO - Setyono, Joko; Sadewa, A Hamim; Madiyan, Maliyah (MANDALA of Health, 2010)
The infiltration of the glomeruli and interstitium by immunocompetent cells are common finding ofkidney with diabetic nephropathy. On the other hand, there is an increasing synthesis of chemokines andother inflammatory mediators by glomerular and tubular cells in hyperglycemic conditions. Single nucleotidepolymorphisms (SNPs) G46295A of MCP-1 (CCR2 are thought playing a key role in the development ofdiabetic nephropathy in type 2 diabetes. Therefore, the aim of this research is to determine whether the riskof diabetic nephropathy is influenced by polymorphisms of CCR2. In addition, this research is also aimed todetermine whether the gender in the diabetic nephropathy patient is influenced by polymorphisms of CCR2 intype 2 diabetes in Indonesian population especially ethnic of Java. A case-control study was performed,including 60 type 2 diabetes patients, 31 subjects with diabetic nephropathy and 29 subjects with nondiabetic nephropathy in Margono Soekarjo Hospital and Sardjito hospital. Polymorphisms of CCR2 wereanalyzed by PCR-RFLP method. The results were analyzed by chi-square. Amount of male in the casesubjects (67,7%) more than amount of male in control subjects (44,8%). G46295A of MCP-1 (CCR2)receptor gene had higher risk of developing diabetic nephropathy in type 2 diabetes (X2 = 12.308, p =0.002). Male individual carry the GA genotype of CCR2 had significant risk of developing diabeticnephropathy (p = 0.004, OR 9.6). This study showed that G46295A MCP-1 (CCR2) receptor gene had higherrisk of developing diabetic nephropathy in type 2 diabetes in Indonesian population especially ethnics ofJava. Male with G46295A MCP-1 (CCR2) receptor gene were more than female and had higher risk ofdeveloping diabetic nephropathy in type 2 diabetes in Indonesian population, especially Java ethnic.